A Brief Overview of Bioinspired Robust Hydrogel Based Shape Morphing Functional Structure for Biomedical Soft Robotics - Goyal, Rohit; Mitra, Santanu (Frontiers in Materials, 2022)
Biomimetic and soft robotics research has been inspired by many biological organisms focusing on soft structural composites reinforced by stiff constituents. In the case of synthetic soft structural materials, hydrogels are very similar to the biological soft tissues/organs, owing to their “wet and soft” properties, their elastic performance, biodegradability, and biocompatibility. However, the current scope of hydrogel applications is usually hampered by their feeble mechanical properties. Although significant progress has been made in developing intense, challenging, and stretchable hydrogels, it is still challenging to realize the optimal magnitude of physical and mechanical properties altogether in synthetic hydrogels. This review briefly focuses on the hydrogel fibrous shape-morphing composite structure and its functionalities. The nature-inspired, fiber-reinforced soft hydrogel shape-morphing functional composite structure delivers them a cartilage-like anisotropic behavior. They could have broad potential applications in various areas, including tissue engineering, soft robotics, stretchable and bio-integrated electronics, microfluidics, and biomedical devices.